Pigmented epithelioid melanocytoma: report of a case with favourable outcome after a 4-year follow-up period - Pepe, Carla Antonella; Lombardi, Mara; Cortelazzi, Chiara; Aimi, Francesca; Ricci, Roberto; Taglia, Maurizio; Santoro, Silvia; Zucchi, Alfredo; Zambito-Spadaro, Fabio; De Panfilis, Giuseppe; Fabrizi, Giuseppe (Acta Biomedica Atenei Parmensis, 2014)
Background: Pigmented epitheliod melanocytoma (PEM) is a uncommon melanocytoma with unique histopathological features and possibly with a favourable prognosis, because, although sentinel lymph-node metastases may occur, in the great majority of cases described up to now there is no spread beyond regional lymph-nodes. The nature of PEM, its biologic behaviour and its relationships to naevi and melanoma, however, remain to be clearly established, and several Authors suggest that further cases of PEM with long follow-up should be published, in order to better assess the biologic/prognostic characteristics of PEM. Methods and Results: We report a new case of PEM, dealing with an oval, regularly marginated, darkly pigmented, asymptomatic nodule. The dermoscopic pattern showed a homogeneous blue-black pigmentation, without any other dermoscopic sign. The histopathologic analysis showed both isolated and nested oval melanocytes at the junctional level, and a mixture of epitheliod and spindle melanocytes, heavily pigmented, together with numerous melanophages in the dermis, with tendency to periadnexal distribution; cellular atypia was pronounced, but only occasional mitoses were identified in the superficial dermis. After a 4-year follow-up period after excision, no persistent lesion or metastases occurred. Conclusions: The present case suggests that PEM has a distinct histopathologic/diagnostic identity among melanocytic tumours. Although the up-to-now favourable outcome, however, our patient needs a large period of observation, and further studies with long follow-up are needed to better define the biologic/prognostic identity of PEM.